New directions in New Zealand local government (Commonwealth Journal of Local Governance, 2010)
The purpose of this paper is to provide a ‘work in progress’ report on some initiatives emerging from local government practice in New Zealand which should help us consider how we think about the role of local government in a world which is undergoing dramatic change. The starting point is work which the writer undertook with the support of Local Government New Zealand (the national association) and a number of New Zealand councils considering the ‘proper role’ of local government. The context is an ongoing public debate driven substantially by the New Zealand business community from a perspective that this ‘proper role’ should be restricted to the delivery of local public goods, narrowly defined. This has included argument that local governments themselves should be structured substantially to promote the efficient delivery of services generally within the now well understood prescriptions of the ‘new public management’. One implication which the business sector in particular drew in looking at the workings of local government was that there should be economies of scale through further amalgamation of councils (the local government sector having been through a major amalgamation process in 1989 which eliminated a large number of special purpose authorities and reduced the number of territorial local authorities from more than 200 to 73). Debate continues, with the latest manifestation being the National Party led government's proposals for the restructuring of local government within the Auckland region, New Zealand's major metropolitan area. The initiatives discussed in this paper are partly a response, but more significantly a result of selected local authorities reflecting on the nature of their role, and the opportunities for being proactive in using their statutory privileges in ways that could produce benefits for their communities without any associated increase in the cost of local government itself.